2013
DOI: 10.1097/nmd.0b013e3182982ba4
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and Suicidal Ideation and Behavior Among Puerto Rican Older Children and Adolescents

Abstract: There is growing evidence of a positive association between asthma and suicidal ideation and behavior in the general community, although information on this potential association is scarce among adolescents and Puerto Ricans, groups at-risk for both conditions. Data came from wave three of the Boricua Youth Study, a longitudinal study of youth in the Bronx and San Juan conducted from 2000–2004. Logistic regressions for correlated data (GEE) were conducted with asthma predicting suicidal ideation and behavior a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
2
8
0
1
Order By: Relevance
“…Jamaican adolescents living in urban areas reported a higher prevalence of suicidal ideation among than those living in rural areas [78]. This is to contrast what is seen for parasuicide and suicide, which occurred more often in rural areas [4653]. One study examined suicide in a country-level; highest rates were found in in Guyana (22.4 per 100,000) and Suriname (15.3), followed by Trinidad (7.0), Cuba (4.0) and Puerto Rico (3.6) [54].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jamaican adolescents living in urban areas reported a higher prevalence of suicidal ideation among than those living in rural areas [78]. This is to contrast what is seen for parasuicide and suicide, which occurred more often in rural areas [4653]. One study examined suicide in a country-level; highest rates were found in in Guyana (22.4 per 100,000) and Suriname (15.3), followed by Trinidad (7.0), Cuba (4.0) and Puerto Rico (3.6) [54].…”
Section: Resultsmentioning
confidence: 99%
“…Among these, 12 were classified as having moderate risk of bias, 38 as having serious risk of bias, and 11 as having unclear risk of bias. Across depression prevalence, depression score, suicidal ideation and parasuicide, females outnumbered males with only minor exceptions: one study from Haiti found a slightly higher prevalence (92% vs 86.5%) and depression scores (x = 23.4 vs x = 21.1) among males [ 45 ]; and three studies showed slightly more parasuicide in males in Martinique and Puerto Rico [ 46 , 47 , 48 ]. Suicide, however, unanimously occurred more frequently by males across several countries [ 49 – 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…2 As young adults, 6% of these individuals reported a suicide attempt, with 30% reporting repeated attempts. 2 Although we know that adolescents and young adults with a chronic illness experience elevated risk for suicidal thoughts and behaviour (STB) as compared with their healthy peers; [6][7][8][9][10][11] important knowledge gaps remain. First, adolescents and young adults with chronic illness are also at increased risk for psychiatric disorder 12 but the interrelationships among chronic illness, psychiatric disorder, and STB are not well-understood in this segment of the population.…”
Section: Abstract Chronic Disease Emerging Adults Epidemiological Smentioning
confidence: 99%
“…A number of studies in the current review focused on the risk of suicide and suicidal behaviour in children and adolescents suffering from asthma, and indicated that young individuals who are suffering from asthma may be at an increased risk of suicide mortality [23], ideation [18] and attempts [20,24,31]. Studies also explored the potential impact of risk-taking behaviours in this age group, finding that a large percentage of children who experienced suicidal behaviour had engaged in cigarette smoking (40%), marijuana use (60%) and binge drinking (37%) [20].…”
Section: Discussionmentioning
confidence: 99%
“…The three papers focusing solely on suicidal ideation found significant associations between asthma and suicidal ideation in children [17], adults [18] and elderly adults aged >65 years [25]. The majority of studies including both suicidal ideation and attempts found that asthma was associated with increased risk of both ideation and attempts in adults [16,28] and children [20,24,31]. Two of the papers reported less conclusive results: the study by CLARKE et al [22] was the only one to find that asthma was associated with suicidal ideation including attempt(s), but not with suicidal ideation alone.…”
Section: (I=1 Ii=1 Iii=2 Iv=1 V=1)mentioning
confidence: 99%